Islamic Critical Thinking: An Analysis of Its Significance Based on The Al-Quran and Scholarly Views - Junoh, Noraini; Mohamad, Abdul Manam; Mustafa@Busu, Zanirah; Mat Jusoh, Nor Asmira (‘Abqari Journal, 2021)
Critical thinking is a very important intellectual tool that could help a person form arguments, determine the credibility of sources, analyse presumptions or make decisions in various contexts. Hence, this study intended to examine the Western and Islamic critical thinking concepts as well as its significance according to the al-Quran and the views of scholars. The library research method was used extensively for collecting and analysing data, which was sourced from literature by philosophers, psychologists and Islamic scientists, especially those involved in the cognitive field. The conceptual framework was built using the content analysis method. According on the analysis, the importance of Islamic critical thinking based on the al-Quran and views of scholars in the cognitive field were extensively elaborated to assist in the practice of Islamic critical thinking. The study found similarities and differences between Islamic and Western critical thinking. The similarities are from the rational utilization aspect and the difference is from the value of truth aspect, whereby Islamic critical thinking accepts divine deliverance (wahyu) as the main source of reference when thinking so that the product of thinking eventually becomes the absolute truth. Hence, the major significance of Islamic critical thinking is to enhance the faith (iman) and piousness (takwa) towards Allah SWT by contemplating and examining nature. At the same time, critical thinking helps a person to face contemporary challenges and solve problems related to every aspect of life. Moreover, critical thinking activities are greatly demanded in Islam so that the mind bestowed by Allah SWT is not neglected and is used properly without transgressing HIS divine deliverance (wahyu).